Mechanical Trap Surface‐Enhanced Raman Spectroscopy for Three‐Dimensional Surface Molecular Imaging of Single Live Cells. Issue 14 (15th February 2017) - Jin, Qianru; Li, Ming; Polat, Beril; Paidi, Santosh K.; Dai, Aimee; Zhang, Amy; Pagaduan, Jayson V.; Barman, Ishan; Gracias, David H.
Abstract: Reported is a new shell‐based spectroscopic platform, named mechanical trap surface‐enhanced Raman spectroscopy (MTSERS), for simultaneous capture, profiling, and 3D microscopic mapping of the intrinsic molecular signatures on the membrane of single live cells. By leveraging the functionalization of the inner surfaces of the MTs with plasmonic gold nanostars, and conformal contact of the cell membrane, MTSERS permits excellent signal enhancement, reliably detects molecular signatures, and allows non‐perturbative, multiplex 3D surface imaging of analytes, such as lipids and proteins on the surface of single cells. The demonstrated ability underscores the potential of MTSERS to perform 3D spectroscopic microimaging and to furnish biologically interpretable, quantitative, and dynamic molecular maps in live cell populations. Abstract : Individual cells are captured by Au nanostar‐coated micromechanical traps, which fold up and surround the cell surface and function as a surface‐enhanced Raman spectroscopy sensor. Through this non‐invasive label‐free approach, proteins and lipids can be identified on the cell surface, and the spectra can be used to reconstruct a 3D microscopic image of the cellular surface chemical composition.